2008
DOI: 10.1038/nature06492
|View full text |Cite
|
Sign up to set email alerts
|

Precise auditory–vocal mirroring in neurons for learned vocal communication

Abstract: Brain mechanisms for communication must establish a correspondence between sensory and motor codes used to represent the signal. One idea is that this correspondence is established at the level of single neurons that are active when the individual performs a particular gesture or observes a similar gesture performed by another individual. Although neurons that display a precise auditory-vocal correspondence could facilitate vocal communication, they have yet to be identified. Here we report that a certain clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
417
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 384 publications
(443 citation statements)
references
References 42 publications
23
417
1
2
Order By: Relevance
“…2C). Because previous studies have demonstrated that singing-related activity in HVC X neurons transmits motor-related information (Hahnloser et al, 2002;Kozhevnikov and Fee, 2007;Prather et al, 2008) and precedes the vocal events by approximately several tens of milliseconds (Kozhevnikov and Fee, 2007), the relative latencies were defined as follows: when a burst was observed during a silent period between syllables, the relative latency was measured from the onset of the target syllable just preceded by the silent period to the onset of the burst (Fig. 2C, blue tick marks); if a burst was generated while vocalizing the target syllable, the relative latency was measured from the onset of the target syllable to the onset of the burst (Fig.…”
Section: Hvc X Activity In Variable Vocal Sequencesmentioning
confidence: 99%
See 2 more Smart Citations
“…2C). Because previous studies have demonstrated that singing-related activity in HVC X neurons transmits motor-related information (Hahnloser et al, 2002;Kozhevnikov and Fee, 2007;Prather et al, 2008) and precedes the vocal events by approximately several tens of milliseconds (Kozhevnikov and Fee, 2007), the relative latencies were defined as follows: when a burst was observed during a silent period between syllables, the relative latency was measured from the onset of the target syllable just preceded by the silent period to the onset of the burst (Fig. 2C, blue tick marks); if a burst was generated while vocalizing the target syllable, the relative latency was measured from the onset of the target syllable to the onset of the burst (Fig.…”
Section: Hvc X Activity In Variable Vocal Sequencesmentioning
confidence: 99%
“…Information processed in HVC is transmitted by two segregated types of projection neurons (Dutar et al, 1998;Mooney, 2000): HVC RA neurons that project to the robust nucleus of the arcopallium (RA), which relay the information to motor neurons for vocal organs (Nottebohm et al, 1976); and HVC X neurons, which innervate to basal ganglia area X (Nottebohm et al, 1982) and are involved in audition-dependent vocal plasticity (Scharff and Nottebohm, 1991;Brainard and Doupe, 2000). Both types of projection neurons generate sparse burst spikes during singing (Hahnloser et al, 2002;Kozhevnikov and Fee, 2007;Prather et al, 2008). In the awake nonsinging state, however, HVC RA neurons are completely inactive (Hahnloser et al, 2002;Kozhevnikov and Fee, 2007;Prather et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Work on songbirds revealed some neurons are activated by both singing and hearing the same part of song (Prather, Peters, Nowicki, & Mooney, 2008) suggesting the existence of mirror (or mirror-like) neurons in a part of the song nervous system (i.e., HVC parallel of NLC: Jarvis, 2006). Perhaps both auditory processing and vocal motor control mechanisms involving calls are shared also in budgerigars.…”
Section: Possible Neural Mechanismsmentioning
confidence: 99%
“…These intriguing neurons have been recorded in ventral premotor area F5 [52] and inferior parietal lobule (IPL) area PFG [25] in the macaque. Mirror neurons responsive to both the production and perception of song have also been found in the forebrain of the swamp sparrow [54]. Direct recordings in humans are limited, but a recent study found mirror neurons in a wide range of brain areas including supplementary motor area (SMA) and parts of the medial temporal lobe [49].…”
Section: Introductionmentioning
confidence: 99%